Gestation changes sodium pump isoform expression, leading to changes in ouabain sensitivity, contractility, and intracellular calcium in rat uterus. Issue 23 (6th December 2017) - Floyd, Rachel V.; Mobasheri, Ali; Wray, Susan
Abstract: Developmental and tissue‐specific differences in isoforms allow Na +, K + ‐ATPase function to be tightly regulated, as they control sensitivity to ions and inhibitors. Uterine contraction relies on the activity of the Na +, K + ATPase, which creates ionic gradients that drive excitation‐contraction coupling. It is unknown whether Na +, K + ATPase isoforms are regulated throughout pregnancy or whether they have a direct role in modulating uterine contractility. We hypothesized that gestation‐dependent differential expression of isoforms would affect contractile responses to Na +, K + ATPase α subunit inhibition with ouabain. Our aims were therefore: (1) to determine the gestation‐dependent expression of mRNA transcripts, protein abundance and tissue distribution of Na +, K + ATPase isoforms in myometrium; (2) to investigate the functional effects of differential isoform expression via ouabain sensitivity; and (3) if changes in contractile responses can be explained by changes in intracellular [Ca 2+ ]. Changes in abundance and distribution of the Na +, K + ATPase α, β and FXYD1 and 2 isoforms, were studied in rat uterus from nonpregnant, and early, mid‐, and term gestation. All α, β subunit isoforms (1, 2, 3) and FXYD1 were detected but FXYD2 was absent. The α 1 and β 1 isoforms were unchanged throughout pregnancy, whereas α 2 and α 3 significant decreased at term while β 2 and FXYD1 significantly increased from mid‐term onwards. These changes in expression correlated with increased functional sensitivity to ouabain, and parallel changes in intracellular Ca 2+, measured with Indo‐1. In conclusion, gestation induces specific regulatory changes in expression of Na +, K + ATPase isoforms in the uterus which influence contractility and may be related to the physiological requirements for successful pregnancy and delivery. Abstract : Differential expression of Na, K ATPase isoforms regulates sensitivity to ions and inhibitors such as ouabain. Little is known about the regulation of isoform expression in the myometrium during gestation and whether this has a functional effect on ouabain senstivity. We found gestation‐dependent differences in expression of ouabain sensitive isoforms that correlate with altered frequency of contractions and calcium transients upon Na, K ATPase inhibition with ouabain.